Hambatan dan Tantangan dalam Implementasi Program Keselamatan Negara di Sektor Penerbangan Indonesia - Ari Fianto; Rindri Andewi Gati (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
Indonesia is obligated to implement the State Safety Programme (SSP) through the National Aviation Safety Program (PKPN), governed by Ministry of Transportation Regulation No. PM 93 of 2016. Despite this regulatory foundation, PKPN implementation within the Directorate General of Civil Aviation (DJPU) faces significant structural, resource, and institutional barriers. This qualitative descriptive study employs Van Meter and Van Horn's policy implementation model to examine implementation challenges across six dimensions: policy standards and objectives, resources, implementing agency characteristics, communication patterns, implementer dispositions, and external environmental conditions. Findings reveal that policy objectives lack clear outcome-based definitions; human resources, IT infrastructure, and budgetary allocations are insufficient; organizational structure remains ad hoc rather than permanent; communication channels are predominantly informal; and implementer understanding of PKPN is uneven. While operator-level support is relatively adequate, higher-level political commitment is incomplete. The study concludes that PKPN implementation remains suboptimal and requires institutional strengthening through permanent organizational restructuring, enhanced resource allocation, improved inter-agency communication, and closer alignment with ICAO's Eight Critical Elements (CE) framework.